The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1749-6632.2010.05569.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin/vasopressin and gonadotropin‐releasing hormone from cephalopods to vertebrates

Abstract: Recent advances in peptide search methods have revealed two peptide systems that have been conserved through metazoan evolution. Members of the oxytocin/vasopressin-superfamily have been identified from protostomian and deuterostomian animals, indicating that the oxytocin/vasopressin hormonal system represents one of the most ancient systems. In most protostomian animals, a single member of the superfamily shares oxytocin-like and vasopressin-like actions. Co-occurrence of two members has been discovered in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Several invertebrate neuropeptides are similar and/or related to vertebrate peptides (Blumenthal, 2010;Lovejoy and Jahan, 2006;Minakata, 2010;Nässel and Wegener, 2011;Vanden Broeck, 2001;Van Loy et al, 2010). Vertebrate Neuropeptide Y (NPY) is involved in the regulation of diverse physiological processes, such as food intake, energy balance and learning (Benoit et al, 2008;Chee and Colmers, 2008;Hökfelt et al, 2008;Nguven et al, 2011;Redrobe et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Several invertebrate neuropeptides are similar and/or related to vertebrate peptides (Blumenthal, 2010;Lovejoy and Jahan, 2006;Minakata, 2010;Nässel and Wegener, 2011;Vanden Broeck, 2001;Van Loy et al, 2010). Vertebrate Neuropeptide Y (NPY) is involved in the regulation of diverse physiological processes, such as food intake, energy balance and learning (Benoit et al, 2008;Chee and Colmers, 2008;Hökfelt et al, 2008;Nguven et al, 2011;Redrobe et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…It has also been reported that levels of estradiol-17b and progesterone in the ovary of O. vulgaris increased with the gonadosomatic index and the morphological changes of the reproductive system [28]. Therefore, it has been suggested that oct-GnRH induces sexual maturation and oviposition in an endocrine fashion by regulating the sex steroids via oct-GnRHR [12,29]. On the basis of this hypothesis, the oct-GnRH levels in the CNS are predicted to increase in parallel with gonadal maturation.…”
Section: Discussionmentioning
confidence: 95%
“…For example, neuropeptides belonging to the oxytocinvasopressin family not only occur in vertebrates but also in (Minakata 2010). These neuropeptides likely arose prior to the divergence of the Protostomia and Deuterostomia.…”
Section: Gene Classification Into Clusters Of Orthologous Groupsmentioning
confidence: 97%